Joining of Ramor 500 Steel with SAW (Submerged Arc Welding) and its Evaluation of Thermomechanical Analysis in ANSYS Package Software - Taskaya, Semih; Gur, Ali Kaya; Ozay, Cetin (Elsevier, 2019)
ANSYS package software; it is a simulation simulation software which is preferred in engineering fields after the modeling stage and before the prototype is produced. Ramor 500 armor steel; it is classified as a high-strength ballistic protection steel with a hardness of 505-590 HV and a thickness of 2-30 mm. In this study, 3mm thick and 65x55mm Ramor 500 steel which is used as the main combat vehicle in armor steel and armed forces in the market, is used with submerged arc welding (SAW) method of 250 fixed amperes, 20, 25, 30 V voltages and 20, 25, 30 cm/min are combined at welding feed rates. The metallographic microstructure, radiographic examination test, SEM-EDS analysis and weld stitch geometry of the structures formed in the intersection after the joining were performed and the thermomechanical analyzes after the joining process were evaluated in the ANSYS package software. In the results of working; radiographic examination test showed that full penetration was achieved in all welded joints and therefore no macro and micro cracks were observed. In the microstructure analysis, a grain structure was observed. In the form of a homogeneous distribution from the weld stitch to the base material. SEM-EDS analysis showed that elemental phase structures were homogeneously distributed. As a result of the effect of welding stitch geometries on the current strength and velocity, welding width increased while welding width increased, while welding speed increased, width decreased. In the thermomechanical analysis results of ANSYS software, heat inputs in welding stresses increased and elastic and mechanical stresses were quite high and replaced by permanent stresses as a result of deformation.
Keywords: Ramor 500; SAW; ANSYS software; Weld stitch geometry; Thermomechanical